Clinical Presentation and Treatment of Early-Onset Behavior Disorders: The Role of Parent Emotion Regulation, Emotion Socialization, and Family Income. Issue 5 (September 2022) - Highlander, April; Zachary, Chloe; Jenkins, Kaeley; Loiselle, Raelyn; McCall, Madison; Youngstrom, Jennifer; McKee, Laura G.; Forehand, Rex; Jones, Deborah J.
Parent emotion regulation and socialization have been linked to various aspects of child functioning. In the case of early-onset behavior disorders in particular, parent emotion regulation may be an important correlate of the coercive cycle implicated in early-onset behavior disorders thus, symptom presentation at baseline. Further, emotion socialization may be complicated by a pattern of parent-child interactions in which both supportive or unsupportive parenting behaviors in response to behavioral dysregulation may increase vulnerability for problem behavior in the future. Some work suggests standard Behavioral Parent Training may impact parent emotion regulation and socialization. Still little is known, however, about how such processes may vary by family income, which is critical given the overrepresentation of low-income children in statistics on early-onset behavior disorders. This study explored parent emotion regulation, socialization, and family income in a sample of socioeconomically diverse treatment-seeking families of young (3–8 years old) children. Findings suggest relations between parental emotion regulation, socialization, and child behavior although the pattern of associations differed at baseline and post-treatment and varied by family income. Clinical implications and future directions are discussed.